TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DI MALAM HARI DALAM PASAL 365 KUHP (STUDI PUTUSAN NOMOR 19/PID/B/220/PN Jkt.Pst): - - Arief Gunawan; Fachri Bey (Reformasi Hukum Trisakti, 2024)
The research begins with a theft incident on Thursday at 19:00 WIB at Graha Cemapak Mas Kemayoran Apartment, where the suspect, armed with a brown-handled knife, confronted witness Purnamawati Pasaribu. Frightened, the victim complied, resulting in the handover of money. The formulation of the problem in this research is whether or not the perpetrator's actions have fulfilled the elements of Article 365 paragraph (1) Jo. paragraph (2) and whether the imposition of criminal sanctions in Decision Number 19/Pid.B/2020/PN.Jkt.Pst which decided that the defendant violated Article 365 paragraph (1) of the Criminal Code was correct. The research methods are normative juridical, analytical descriptive and qualitative. The results of the research and discussion show that the actions carried out by the sender have fulfilled the formulation of the elements contained in the indictment of Article 365 paragraph (1) Jo. paragraph (2) of the Criminal Code. The conclusion of this research is that the decision that provides a prison sentence of 1 year and 6 months is not appropriate, and the defendant should be subject to the provisions of Article 365 paragraph (1) in conjunction with paragraph (2) number 1 of the Criminal Code with a maximum prison sentence of 12 years.